Portuguese migrants in Switzerland: healthcare and health status compared to Portuguese residents - Alves, L (2013)
Background: Most migrant studies have compared health characteristics between migrants and nationals of the host country. We aimed at comparing health characteristics of migrants with nationals from their home country. Methods: Portuguese national health survey (2005-6; 30,173 participants aged 18-75 years) and four national health surveys conducted in Switzerland (2002, 2004, 2007 and 2011, totalling 1,170 Portuguese migrants of the same age range). Self-reported data on length of stay, cardiovascular risk factors, healthcare use and health status were collected. Results: Resident Portuguese were significantly older and more educated than migrants. Resident Portuguese had a higher mean BMI and prevalence of obesity than migrants. Resident Portuguese also reported more frequently being hypertensive and having their blood pressure screened within the last year. On the contrary, migrant Portuguese were more frequently smokers, had a medical visit in the previous year more frequently and self-rated their health higher than resident Portuguese. After adjustment for age, gender, marital status and education, migrants had a higher likelihood of smoking, of having a medical visit the previous year, and of self-rating their current health as good or very good than resident Portuguese. Compared to Portuguese residents, cholesterol screening in the previous year was more common only among migrants living in Switzerland for more than 17 years. Conclusion: Portuguese migrants in Switzerland do not differ substantially from resident Portuguese regarding most cardiovascular risk factors. Migrants consider themselves healthier than Portuguese residents and more often had a recent medical visit.